The Effect of Auditor Commitment on Supply Chain Performance: Moderating Role of Supply Chain Top Management Support - Didiet Rachmat Hidayat, Raden; Azis, Yudi; Yunizar, Yunizar; Amzal, Cupian (International Journal of Supply Chain Management, 2020)
The foremost aim of the present study is to examine the influence of internal audit competency along with internal and external auditor and employee commitment to change on the supply chain performance of the audit companies in Jakarta Indonesia. The objectives also include the examination of moderating role of supply chain top management support among the links of internal audit competency, internal and external auditor, employee commitment to change and supply chain performance of the audit companies in Jakarta Indonesia. The data has been obtained by using the questionnaire method while analysis has been made by using the smart-PLS. The results revealed that all the predictors such as internal audit competency, internal and external auditor, and employee commitment to change have a positive association with supply chain performance. The results also showed that the supply chain top management support has positively moderated among the links of internal audit competency and supply chain performance. These findings are provided with the guideline to the upcoming studies along with the regulators while investigating this area in future and formulating the policies on the supply chain performance of the organization.Â